E-Waste Management in Northern Coimbatore, India: A Pilot Study - P. Krithiga; V. Sridharan; C. Thamarai Selvan; S. Surenthar (Research Developments in Science and Technology Vol. 5, 2022)
The electronic industry is the larger and fastest-growing production in the world. Discarded Waste Electrical and Electronic equipment (WEEE) is used as products with all of their parts at the end of their lifespan are called E-waste. Most electronic items like PC, Mobile Phones, Circuit Boards, Toys, cables, etc. are regularly used, and buying a new product, has to rise in more amount of E-waste. People do not know how to manage this rejected e-waste. Most people are not conscious of the hazardous effect created by e-waste on human health as well as on the environment. The objective of the study is to investigate the awareness level in e-waste disposal and management. The study governs a preliminary work conducted in Coimbatore city to check the awareness level of E-waste. The data concerning E-waste in Coimbatore was obtained through individual field visits, networks with people, and authentic records maintained by the firm. The Questionnaire survey was prepared among the consumers and recyclers about the hazardous level of E-waste. Finally, conclude with some mitigation measures on E-waste.